Penerapan Akad Istisna pada Jual Beli Sampan - Ayuda Ayuda; Nurse Fatimah MZ; Ferdinan Ferdinan (AL-Muqayyad, 2021)
People often have buying and selling carried out to obtain convenience, without knowing whether buying and selling is in accordance with or contrary to Islamic teachings. As happened in the practice of buying and selling istishna. This study aims to determine the application of the Istisna contract in the sale and purchase of canoes in Simpang Gaung Village, Guang District, Indragiri Hilir Regency. The research is field research using qualitative methods. The system of buying and selling canoes in Simpang Gaung Village is partly in accordance with the istisna contract. Meanwhile, seen in the application of the contract, the istisna contract has not been implemented properly, especially in the agreement on the contract and the supply of goods. So, it can be concluded that the sale and purchase of canoes at the Echo intersection are still not in accordance with the istisna contract